Pathology - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
The presence of diseases, changes in severity, and the performance of cassava clones in 5 different ecosystems were studied. A wide-type resistance to existing biotic problems and its durability in these ecosystems were investigated. The relationship between plant reaction to CBB (Xanthomonas campestris pv. manihotis) in the greenhouse and in the field, and its stability through several continuous cycles was investigated. The differences in the severity of CBB, superelongation [Sphaceloma manihoticola (Elsinoe sp.)], and anthracnose (Glomerella manihotis) in monoclonal and multiclonal plots at high and low inoculum levels were also examined. Root and stem rot caused by Diplodia manihotis, which could be synonymous with Botryodiplodia manihoticola, was identified. Confirmation of this synonymy awaits further taxonomic study. Studies on the characterization of the causal agent of the frog skin disease continued with emphasis on detection, transmission, and isolation. Furthermore, the variation encountered in the field within and among cv. regarding their susceptibility to deterioration was studied and the biochemical processes which leadto physiological deterioration were analyzed. (CIAT)